2019
DOI: 10.3171/2019.6.focus19294
|View full text |Cite
|
Sign up to set email alerts
|

Multimaterial and multicolor 3D-printed model in training of transnasal endoscopic surgery for pituitary adenoma

Abstract: OBJECTIVEThe aim of the present study was to investigate the practical value of a multimaterial and multicolor 3D-printed model in anatomical teaching, surgical training, and preoperative planning of transnasal endoscopic surgery for pituitary adenoma.METHODSMultimodality neuroimaging data were obtained in a 42-year-old healthy male volunteer and a 40-year-old female patient with an invasive nonfunctional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In a previous study of patients with malignant brain tumors (glioma), a 3D printing approach was shown to improve patient understanding and support clinical decision making [ 28 ]. For patients with pituitary tumors 3D printed anatomical models have been proposed for enhancing surgical training [ 23 , 24 ]. A particular focus of these early models has been the visual appearance and aesthetics with respect to mimicking human tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study of patients with malignant brain tumors (glioma), a 3D printing approach was shown to improve patient understanding and support clinical decision making [ 28 ]. For patients with pituitary tumors 3D printed anatomical models have been proposed for enhancing surgical training [ 23 , 24 ]. A particular focus of these early models has been the visual appearance and aesthetics with respect to mimicking human tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems unlikely that this type of anatomical model would be readily adopted into routine clinical practice. Specifically, the lack of colors depicting the different structures was considered a significant limitation, and is something which has been highlighted by other workers [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With advanced in 3D printing technology and manufacturing many 3D organ models have been developed for surgical training, including temporal bone (6)(7)(8), paranasal sinuses (9-12), skull base (9,(13)(14)(15)(16), kidney, renal pelvis, and ureter (17), mandibular (9), aorta (18), and heart (19). In addition, some models successfully reproduce the organs with pre-existing pathology such as cerebral aneurysms (20,21) and basilar invagination (22).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The design and fabrication of cerebral vascular phantoms using additive manufacturing for neurosurgery have already been reported in the literature. 13,[19][20][21][22] The most representative examples are mainly related to surgical aid applications (e.g., aneurysm clipping 20,23 ) as well as to diagnosis, 24,25 blood circulation analysis, 26,27 and patients' information purposes. 12 The manufacturing strategies explored included material extrusion of thermoplastic polymers (e.g., fused filament fabrication [FFF] 20,28 ), VAT photopolymerization, 29,30 PolyJet printing, 31,32 and sacrificial approaches combining FFF of acrylonitrile butadiene styrene (ABS) templates and casting of silicone-based materials.…”
Section: Introductionmentioning
confidence: 99%